FEMALE BOARDROOM PARTICIPATION AND EARNINGS MANAGEMENT OF LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
This study ascertained the effect of female boardroom participation on earnings management of listed manufacturing firms in Nigeria from 2012-2021. Specifically, this study determined the effect of female chief executive officer, female non-executive director and female executive director on discretionary accruals. Panel data were used in this study, which were obtained from the annual reports and accounts of the twenty (21) listed manufacturing firms for the periods 2012-2021. Ex-Post Facto research design was employed. Descriptive statistics of the dataset from the sampled firms was employed to summarily describe the mean, standard deviation, minimum and maximum values of the data for the study variables. Inferential statistics using Pearson correlation coefficient and Panel least square regression analysis were employed to test the hypotheses of the study. The results showed that female chief executive officer has a strong significant but negative effect on discretionary accruals (β1 = -0.040633; p-value = 0.0082); female non-executive director has a strong significant but negative effect on discretionary accruals (β2 = -2.208115; p-value = 0.0000); female executive director has a strong significant but negative effect on discretionary accruals (β3 = -1.159706; p-value = 0.0000) of listed manufacturing firms in Nigeria at 5% level of significance respectively.  The study recommended inter alia the recruitment of an ample number of females in the top-notch positions of the board to create a gender-diverse management team to reap the benefits of leadership styles of both genders.
Keywords: Discretionary Accruals; Earnings Management; Female Boardroom Participation; Female Chief Executive Officer; Female Executive Director; Female Non-Executive Director